The effect of silicon, silica and silicates on the osteoblast in vitro - Anderson, Susan Ita (2001)
Silica is an essential trace element in human nutrition and dietary deficiency leads to abnormal bone formation in experimental animal studies (Carlisle, 1972, Schwartz 1972). Silica-containing glasses and glass ceramics, within a certain range, are bioactive, forming a strong bond with bone and soft tissue when they are used as bone replacement materials. The aim of this work was to investigate the effect of silica on the osteoblast in vitro with a view to its eventual incorporation into biomaterials to improve bone-bonding properties. Two distinct approaches were used. The first involved the analysis of silica as a nutrient, by supplementing osteoblast growth medium with sodium metasilicate, and evaluating the osteoblast response in terms of cell growth, mineralisation and cytotoxicity. The second approach examined the response of osteoblasts to silica as a biomaterial. A silica gel was used to isolate the effects of silica on the osteoblast in vitro without the effects of the other ions present in bioactive glass. The biocompatibility of patterned silicon wafers was investigated to evaluate the potential use of these materials in the field of biomaterials. Finally, the bioactivity and osteoblast response to a novel silicon/polymer composites as assesseda s a potential biomaterial. The results of nutrition studies showed that in some cases low levels (1-100ppm) of silicate appeared to have a beneficial effect on bone formation in terms of nodule formation and mineralisation. Higher levels of silicate supplementation (>300ppm) caused rapid apoptosis in osteoblasts, fibroblasts and macrophages and affected cell spreading. The biomaterial studies showed that the silica gel surface was bioactive and osteoblasts responded favourably demonstrating enhanced, earlier nodule formation. Bioactive surfaces formed a calcium phosphate (CaPi) layer and released silicic acid when incubated in a simulated body fluid (SBF). Bulk silicon wafers (Si) supported osteoblast growth however, the removal of the oxide layer by wet etching (ESi) imparted bioactive properties to the wafer. Patterned Si/Esi surfaces supported the formation of a CaPi layer over the entire surface and demonstrated osteoblast preferences for bioactive surfaces. The incorporation of silica particles into a bioabsorbable polymer matrix rendered the composite bioactive and supported osteoblast growth. The results of this work demonstrate the importance of silica in bone mineralisation, osteoblast apoptosis and particularly the potential benefits of the use of silica and silicon to improve bone bonding in non-bioactive biomaterials and biosensors.